The interplay of ferroelectricity and magneto-transport in non-magnetic moiré superlattices - Siqi Jiang; Renjun Du; Jiawei Jiang; Gan Liu; Jiabei Huang; Yu Du; Yaqing Han; Jingkuan Xiao; Di Zhang; Fuzhuo Lian; Wanting Xu; Siqin Wang; et al. (Nature Communications)
Abstract The coupling of ferroelectricity and magnetic order provides rich tunability for engineering material properties and demonstrates great potential for uncovering novel quantum phenomena and multifunctional devices. Here, we report interfacial ferroelectricity in moiré superlattices constructed from graphene and hexagonal boron nitride. We observe ferroelectric polarization in an across-layer moiré superlattice with an intercalated layer, demonstrating a remnant polarization comparable to its non-intercalated counterpart. Remarkably, we reveal a magnetic-field enhancement of ferroelectric polarization that persists up to room temperature, showcasing an unconventional amplification of ferroelectricity in materials lacking magnetic elements. This phenomenon, consistent across devices with varying layer configurations, arises purely from electronic rather than ionic contributions. Furthermore, the ferroelectric polarization in turn modulates quantum transport characteristics, suppressing Shubnikov-de Haas oscillations and altering quantum Hall states in polarized phases. This interplay between ferroelectricity and magneto-transport in non-magnetic materials is crucial for exploring magnetoelectric effects and advancing two-dimensional memory and logic applications.